"So Much Technology, So Little Talent"? Skills for Harnessing Technology for Leadership Outcomes. Issue 2 (August 2014) - Phelps, Kirstin C.
<x xml:space="preserve">Abstract</x> Advanced information and communication technologies are impacting the ways groups and individuals collaborate, communicate, and engage. Such changes also have impacts on the leadership process. By reviewing the literature on e‐leadership and technology‐centered fields, the current article provides recommendations and implications for leading in online environments.